Terminal Epitope-Dependent Branch Preference of Siglecs Toward N-Glycans - Wang, Shuaishuai; Chen, Congcong; Guan, Minhui; Liu, Ding; Wan, Xiu-Feng; Li, Lei (Frontiers in Molecular Biosciences, 2021)
Siglecs are sialic acid-binding immunoglobulin-like lectins that play vital roles in immune cell signaling. Siglecs help the immune system distinguish between self and non-self through the recognition of glycan ligands. While the primary binding specificities of Siglecs are known to be divergent, their specificities for complex glycans remain unclear. Herein, we determined N-glycan binding profiles of a set of Siglecs by using a complex asymmetric N-glycan microarray. Our results showed that Siglecs had unique terminal epitope-dependent branch preference when recognizing asymmetric N-glycans. Specifically, human Siglec-3, -9, and -10 prefer the a1-3 branch when Siaa2-6Galb1-4GlcNAc terminal epitope serves as the binding ligand, but prefer the opposite a1-6 branch when Siaa2-3Galb1-4GlcNAc epitope serves as the ligand. Interestingly, Siglec-10 exhibited dramatic binding divergence towards a pair of Neu5Ac-containing asymmetric N-glycan isomers, as well as their Neu5Gc-containing counterparts. This new information on complex glycan recognition by Siglecs provides insights into their biological roles and applications.